Dynamics of waste-to-energy incineration R&D collaboration networks: a social network analysis based on patent data. Issue 2 (4th March 2017) - Ma, Ding; Yu, Yongsheng; Liu, Si-shi; Zhang, Ya-rui
Abstract: The municipal solid waste in China is increasing at an unprecedented pace due to the upgrading urbanization and improving living standard. The waste-to-energy (WTE) incineration technology offers a viable and potentially profitable technical solution to this booming phenomenon. The highly complex and systematic nature of WTE technologies have led to the emergence of WTE innovation network in the past decade. This study applies complex network theory as well as social network analysis to investigate the social network structure evolution of WTE technologies in terms of global network properties, major actors' centrality and collaboration relationships. Based on the data-set covering joint filing patents pertaining to waste heat over the period 2006–2015, this study finds that the overall WTE innovation network exhibits the properties of scale-free network with minority organizations linking to abundant organizations. A large fraction of major actors represent the first-movers in the WTE research and still control the technological trajectories. The collaboration relationships have moved toward higher level of multidisciplinary and larger technological distance. Overall, the evolution of WTE innovation network features a young state of industry with high regime dependence. Finally, some suggestions are proposed to shed light on benign development of WTE innovation network.